Mercaptopyridine modified monolithic column

By grafting pyridine groups on the epoxy resin-based whole column material and performing specific treatment, the problems of low separation yield and poor stability of nucleic acid substances in the prior art are solved, and efficient and low-cost nucleic acid substance enrichment and Separation effect.

CN119280889APending Publication Date: 2025-01-10YU JI (SHANGHAI) BIOLOGICAL TECH CO LTD

Patent Information

Application Number
CN202411449266.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-05-10
Filing Date
2024-10-17
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing monolithic column materials have low yields in terms of separation and enrichment of nucleic acid substances, poor stability, inconsistent linear amplification and reproducibility, and the temperature control of the curing and forming process is complex and the cycle is long, resulting in high costs.

Method used

The epoxy resin-based monolithic column material is used and pyridine groups are grafted on its surface. The specific adsorption capacity of nucleic acid substances is improved through hydroxylation, epoxidation and pyridine modification treatment.

Benefits of technology

It has achieved the enrichment and separation of nucleic acid substances with high yield, high flow rate and low operating pressure, uniform pore distribution and good toughness, shortening the process cycle and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005088597540000071
    Figure BDA0005088597540000071
  • Figure BDA0005088597540000072
    Figure BDA0005088597540000072
  • Figure BDA0005088597540000081
    Figure BDA0005088597540000081
Patent Text Reader

Abstract

The invention discloses a monolithic column material. Pyridine groups are grafted on the inner surfaces of pores and channels in the monolithic column material. The pyridyl exists in the form of EP-OCH2CH (OH) CH-SPy, and the structural formula is shown in the description. The monolithic column prepared by the invention is rich in hydroxyl groups, has excellent compatibility to an elution object containing biomacromolecules, has excellent specific adsorption capacity for nucleic acid substances, and is suitable for enrichment and separation of DNA and / or RNA substances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a monolithic column material, and more specifically, to a monolithic column material for nucleic acid enrichment and separation. Background Art

[0002] At present, the separation and purification of biomolecules are basically achieved by modifying the surface ligands of chromatographic microsphere media to achieve separation and purification of different functions, so as to obtain relatively pure molecules as medicines, diagnostic reagents, biochemical process raw materials, food, cosmetic additives, etc. However, microsphere media as stationary phases have the following disadvantages: 1) The pore distribution is relatively small, and the separation ability for biomolecules with large molecular weight is poor; 2) The diffusion effect of chromatographic microspheres is obvious, and a long retention time is required to fully diffuse to the theoretical specific surface area of ​​the microspheres, which takes longer for biomolecules; 3) The working pressure of the chromatographic column filled with microspheres is high, which is not conducive to the efficient operation of the system.

[0003] Monolith technology is a new generation of chromatographic stationary phase developed in recent years. It currently has obvious advantages over traditional porous microsphere filling media in the rapid separation and purification of biomacromolecules. The monolith consists of a whole block of highly connected pipes, and the fluid flows in the evenly distributed pipes. The monolith matrix is ​​composed of polymers, and the average diameter of its internal pipes is 2μm. Inside the monolith, each pipe is connected to dozens of other pipes. The high connectivity of the pipes helps to evenly distribute the fluid, reduce the operating pressure, and achieve high flow rate and low column pressure.

[0004] At present, the materials of the monolithic column are polymethacrylate polymers or polystyrene polymers. They currently have many commercially successful products on the market, which are relatively successful monolithic column solutions. However, polymethacrylate polymers and polystyrene polymers also have the following problems: 1) The molding temperature is high. When preparing larger size blocks, the process control is complicated due to the thermal effect, the distribution uniformity of the cut channels is poor, and the pore size double distribution phenomenon may occur. In addition, the curing molding is generally at 60-80°C, the time is 12-24 hours, and the cycle is long; 2) After curing molding, the hydrophobicity is strong. In the process of biomacromolecule purification, the non-specific adsorption phenomenon is more obvious. Generally, hydrophilic modification (such as using hydroxyl-rich molecules) is required to reduce the problem of non-specific adsorption; 3) When solidified into a larger pore size, due to its poor toughness, it is easy to be damaged, affecting the use effect. These are the technical problems that monolithic columns will encounter when facing the enrichment and separation of biomacromolecules, and they are also the technical problems that the present invention wants to solve.

[0005] CN202211600949.6 discloses a chromatography material based on epoxy resin, which has uniform internal structure, good preparation reproducibility, high toughness, modifiable functional ligands and high hydrophilicity. CN113145088A discloses a hydrophilic monolithic material and its preparation and application, wherein the monomer triglycidylisocyanurate (TGIC) and 1,4,7,10-tetraazacyclododecane (1,4,7,10-Tetraazacyclododecane, cyclen) are ultrasonically dissolved in an organic solvent, and then an epoxy-amine ring-opening polymerization reaction is carried out under heating conditions to form a monolithic material. Since epoxy reacts with amines to generate a large amount of hydroxyl groups, the monolithic material obtained has good hydrophilicity. EP2485836A1 discloses a monolithic column with fixed monomeric avidin for enriching and identifying biotinylated species, which comprises a stationary phase made of a monolithic material containing a reactive group, and avidin is bound to it, monomerized and renatured.

[0006] At present, when facing the separation of biological macromolecules, especially when facing the enrichment and separation of nucleic acid substances from mixed materials including proteins and nucleic acids, the monolithic column needs to further improve the specific adsorption of biological macromolecules on the basis of general excellent adsorption performance, uniform results, low operating pressure and high flow rate. Summary of the invention

[0007] The technical problem to be solved by the present invention is to overcome the existing technology that the monolithic column is not optimized for biomacromolecules, especially nucleic acid substances, so the yield is low (generally 60%-80%), the stability is poor, the linear amplification reproducibility is inconsistent, and the optimization and control of the purification process are complex. In addition, the temperature control of the curing molding process is complex, the curing cycle is long, etc., resulting in high costs. An epoxy resin-based monolithic column material with specific adsorption capacity for nucleic acids is proposed, which retains the characteristics of excellent adsorption performance, uniform results, low operating pressure, and high flow rate of the epoxy resin monolithic column material, and also has excellent specific enrichment ability for nucleic acid substances.

[0008] To achieve the above objectives, the present invention proposes the following technical solutions.

[0009] The first aspect of the present invention provides an integral column.

[0010] A monolithic column has pyridine groups grafted onto the inner surfaces of the pores and channels.

[0011] In some embodiments, the pyridine group is present in the form of EP-OCH2CH(OH)CH-SPy.

[0012] in:

[0013] EP is epoxy resin, Py is a substituted or unsubstituted pyridine ring;

[0014] The unsubstituted pyridine ring, that is, the basic skeleton or the functional group to which the object is attached, has only hydrogen atoms or deuterium atoms thereof.

[0015] The substituents in the substituted pyridine ring are alkyl, cycloalkyl, heterocyclic, alkenyl, cycloalkenyl, alkynyl, aryl, heteroaryl, hydroxyl, thiol, alkoxy, alkylthio, aryl ether, aryl thioether, halogen, cyano, aldehyde, acyl, carboxyl, ester, amide, sulfonyl, sulfonate, sulfonamide, amino, nitro, and silane.

[0016] The saturated aliphatic hydrocarbon groups such as the alkylmethyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, etc. may be substituted or unsubstituted. The additional substituents when substituted are not particularly limited, and examples thereof include alkyl, halogen, aryl, heteroaryl, etc., and the same is true in the following descriptions. In addition, the carbon number of the alkyl group is not particularly limited, and in terms of ease of acquisition or cost, it is preferably in the range of 1 or more and 20 or less, and more preferably in the range of 1 or more and 8 or less.

[0017] The cycloalkyl group refers to a saturated alicyclic hydrocarbon group such as cyclopropyl, cyclohexyl, norbornyl, and adamantyl, which may be substituted or unsubstituted. The number of carbon atoms in the cycloalkyl group is not particularly limited, but is preferably within a range of 3 or more and 20 or less.

[0018] The heterocyclic group refers to an aliphatic ring having atoms other than carbon in the ring, such as a pyran ring, a piperidine ring, and a cyclic amide, and may be substituted or unsubstituted. The number of carbon atoms in the heterocyclic group is not particularly limited, but is preferably in the range of 2 or more and 20 or less.

[0019] The alkenyl group refers to an unsaturated aliphatic hydrocarbon group containing a double bond, such as a vinyl group, an allyl group, and a butadienyl group, and may be substituted or unsubstituted. The number of carbon atoms in the alkenyl group is not particularly limited, but is preferably in the range of 2 or more and 20 or less.

[0020] The cycloalkenyl group refers to an unsaturated alicyclic hydrocarbon group containing a double bond, such as cyclopentenyl, cyclopentadienyl, and cyclohexenyl, which may be substituted or unsubstituted. The number of carbon atoms in the cycloalkenyl group is not particularly limited, but is preferably in the range of 3 or more and 20 or less.

[0021] The alkynyl group refers to an unsaturated aliphatic hydrocarbon group containing a triple bond, such as an ethynyl group, which may be substituted or unsubstituted. The number of carbon atoms in the alkynyl group is not particularly limited, but is preferably in the range of 2 or more and 20 or less.

[0022] The so-called aryl group may be any one of a monocyclic ring or a condensed ring, for example, phenyl, naphthyl, fluorenyl, benzofluorenyl, dibenzofluorenyl, phenanthryl, anthracenyl, triphenylenyl, benzanthryl, pyrenyl, fluoranthene, triphenylene (triphenylenyl group), benzofluoranthene, dibenzoanthryl, peryl, helicenyl group and other aromatic hydrocarbon groups. Among them, preferably phenyl, naphthyl, fluorenyl, phenanthryl, anthracenyl. The aryl group may be substituted or unsubstituted. The carbon number of the aryl group is not particularly limited, preferably 6 or more and 40 or less, more preferably 6 or more and 30 or less. In addition, in the phenyl group, when there are substituents on the two adjacent carbon atoms in the phenyl group, these substituents may form a ring structure with each other. As a result, the formed group may correspond to any one or more of "substituted phenyl group", "aryl group having a structure in which two or more rings are condensed", and "heteroaryl group having a structure in which two or more rings are condensed" depending on its structure.

[0023] The so-called heteroaryl group may be any of a monocyclic ring or a condensed ring, for example, a cyclic aromatic group having atoms other than carbon and hydrogen, i.e., heteroatoms, such as pyridyl, furyl, thienyl, quinolyl, isoquinolyl, pyrazinyl, pyrimidinyl, pyridazinyl, triazinyl, naphthyridinyl, cinnolinyl, phthalazinyl, quinoxalinyl, quinazolinyl, benzofuranyl, benzothienyl, indolyl, dibenzofuranyl, dibenzothienyl, carbazolyl, benzocarbazolyl, carbolinyl group, indolecarbazolyl, benzofuranocarbazolyl, benzothienocarbazolyl, dihydroindenocarbazolyl, benzoquinolyl, acridinyl, dibenzoacridinyl, benzimidazolyl, imidazopyridyl, benzoxazolyl, benzothiazolyl, phenanthrolinyl, etc., in one or more rings. The heteroatom is preferably a nitrogen atom, an oxygen atom or a sulfur atom. The heteroaryl group may be substituted or unsubstituted. The number of carbon atoms in the heteroaryl group is not particularly limited, but is preferably in the range of 2 to 40, more preferably in the range of 2 to 30.

[0024] The alkoxy group refers to a functional group in which an aliphatic hydrocarbon group is bonded via an ether bond, such as a methoxy group, an ethoxy group, a propoxy group, etc., and may be substituted or unsubstituted. The number of carbon atoms in the alkoxy group is not particularly limited, but is preferably in the range of 1 or more and 20 or less.

[0025] The so-called alkylthio group refers to an alkoxy group in which the oxygen atom of the ether bond is replaced by a sulfur atom. It may be substituted or unsubstituted. The carbon number of the alkylthio group is not particularly limited, but is preferably in the range of 1 or more and 20 or less.

[0026] The aryl ether group refers to a functional group in which an aromatic hydrocarbon group is bonded via an ether bond, such as a phenoxy group, and may be substituted or unsubstituted. The number of carbon atoms in the aryl ether group is not particularly limited, but is preferably in the range of 6 or more and 40 or less.

[0027] The so-called aryl thioether group refers to an aryl ether group in which the oxygen atom of the ether bond is substituted with a sulfur atom. It may be further substituted. The carbon number of the aryl thioether group is not particularly limited, but is preferably in the range of 6 or more and 40 or less.

[0028] The halogen refers to an atom selected from fluorine, chlorine, bromine and iodine.

[0029] The cyano group refers to a functional group represented by a structure of -C≡N. Here, the carbon atom is bonded to the other functional group.

[0030] The aldehyde group refers to a functional group represented by a structure of -C(=O)H. Here, the carbon atom is bonded to another functional group.

[0031] The so-called acyl group refers to a functional group such as acetyl, propionyl, benzoyl, acryloyl, etc., which is bonded to an alkyl, cycloalkyl, alkenyl, alkynyl, aryl, or heteroaryl group via a carbonyl group, and may be further substituted. The number of carbon atoms in the acyl group is not particularly limited, but is preferably 2 or more and 40 or less, and more preferably 2 or more and 30 or less.

[0032] The so-called ester group refers to a functional group formed by an ester bond such as an alkyl group, a cycloalkyl group, an aryl group, a heteroaryl group, etc., which may be further substituted. The carbon number of the ester group is not particularly limited, and is preferably in the range of 1 to 20. More specifically, it includes: methyl ester groups such as methoxycarbonyl, ethyl ester groups such as ethoxycarbonyl, propyl ester groups such as propoxycarbonyl, butyl ester groups such as butoxycarbonyl, isopropyl ester groups such as isopropoxymethoxycarbonyl, hexyl ester groups such as hexyloxycarbonyl, phenyl ester groups such as phenoxycarbonyl, etc.

[0033] The so-called amide group refers to a functional group formed by an alkyl group, a cycloalkyl group, an aryl group, a heteroaryl group, etc. through an amide bond, which may be further substituted. The carbon number of the amide group is not particularly limited, but is preferably in the range of 1 to 20. More specifically, methylamide group, ethylamide group, propylamide group, butylamide group, isopropylamide group, hexylamide group, phenylamide group, etc. can be cited.

[0034] The sulfonyl group refers to a functional group such as an alkyl group, a cycloalkyl group, an aryl group, a heteroaryl group, etc., which is bonded via a -S(=O)2- bond and may be further substituted. The carbon number of the sulfonyl group is not particularly limited, but is preferably in the range of 1 or more and 20 or less.

[0035] The so-called sulfonate group refers to a functional group formed by bonding an alkyl group, a cycloalkyl group, an aryl group, a heteroaryl group, etc. via a sulfonate bond. Here, the so-called sulfonate bond refers to a carbonyl part of an ester bond, that is, -C(=O)-, which is substituted by a sulfonyl part, that is, -S(=O)2-. In addition, it may be further substituted. The carbon number of the sulfonate group is not particularly limited, and is preferably in the range of 1 or more and 20 or less.

[0036] The so-called sulfonamide group refers to a functional group formed by bonding an alkyl group, a cycloalkyl group, an aryl group, a heteroaryl group, etc. via a sulfonamide bond. Here, the so-called sulfonamide bond refers to a carbonyl part of an amide bond, i.e., -C(=O)-, which is substituted with a sulfonyl part, i.e., -S(=O)2-. In addition, it may be further substituted. The carbon number of the sulfonamide group is not particularly limited, but is preferably in the range of 1 or more and 20 or less.

[0037] The amino group refers to a substituted or unsubstituted amino group. As a substituent in the case of substitution, for example, an aryl group, a heteroaryl group, a straight-chain alkyl group, and a branched alkyl group can be cited. Here, as the aryl group and the heteroaryl group, preferably a phenyl group, a naphthyl group, a pyridyl group, and a quinolyl group. In addition, it can be further substituted. The carbon number is not particularly limited, and is preferably in the range of 2 or more and 50 or less, more preferably in the range of 6 or more and 40 or less, and particularly preferably in the range of 6 or more and 30 or less.

[0038] The so-called silyl group refers to a functional group bonded with a substituted or unsubstituted silicon atom, for example, an alkylsilyl group such as a trimethylsilyl group, a triethylsilyl group, a tert-butyldimethylsilyl group, a propyldimethylsilyl group, a vinyldimethylsilyl group, or an arylsilyl group such as a phenyldimethylsilyl group, a tert-butyldiphenylsilyl group, a triphenylsilyl group, a trinaphthylsilyl group. In addition, it may be further substituted. The carbon number of the silyl group is not particularly limited, but is preferably in the range of 1 or more and 30 or less.

[0039] In some embodiments, the substituent in the substituted pyridine ring is methyl, sulfonamide, carboxyl or nitro.

[0040] In some embodiments, the -Spy is derived from one or more of 2-mercaptopyridine, 4-mercaptopyridine, 2-mercapto-5-nitropyridine, 6-methylpyridine-2-thiol, 6-mercaptopyridine-3-carboxylic acid, 4-mercaptopyridine-3-sulfonamide, and 6-mercaptopyridine-3-sulfonamide.

[0041] In some embodiments, the pore size of the monolithic column is 2 μm-6 μm, preferably 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm, 4.0 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm, 5.0 μm, 5.1 μm, 5.2 μm, 5.3 μm, 5.4 μm, 5.5 μm, 5.6 μm, 5.7 μm, 5.8 μm, 5.9 μm, 6. .8μm, 3.9μm, 4.0μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9 μm, 5.0μm, 5.1μm, 5.2μm, 5.3μm, 5.4μm, 5.5μm, 5.6μm, 5.7μm, 5.8μm, 5.9μm, 6.0μm.

[0042] In some embodiments, the pore volume of the integral column is 1.1 mL / g-1.8 mL / g, preferably 1.10 mL / g, 1.15 mL / g, 1.20 mL / g, 1.25 mL / g, 1.30 mL / g, 1.35 mL / g, 1.40 mL / g, 1.45 mL / g, 1.50 mL / g, 1.55 mL / g, 1.60 mL / g, 1.65 mL / g, 1.70 mL / g, 1.75 mL / g, 1.80 mL / g.

[0043] In some embodiments, the porosity of the integral column is 55%-68%, preferably 55.0%, 55.5%, 56.0%, 56.5%, 57.0%, 57.5%, 58.0%, 58.5%, 59.0%, 59.5%, 60.0%, 60.5%, 61.0%, 61.5%, 62.0%, 62.5%, 63.0%, 63.5%, 64.0%, 64.5%, 65.0%, 65.5%, 66.0%, 66.5%, 67.0%, 67.5%, 68.0%.

[0044] In some embodiments, the raw material of the monolithic column includes a substance A containing multiple epoxy groups.

[0045] The substance containing multiple epoxy groups refers to a substance containing two or more epoxy groups in its structure.

[0046] In some embodiments, the substance containing multiple epoxy groups is preferably a polyepoxy glycidyl ether substance, or a polyepoxy glycidyl ester substance.

[0047] In some embodiments, the glycidyl ether substance may be one or more monomers satisfying the following structural formula I:

[0048]

[0049] In structural formula Ⅰ, R 1 is selected from hydrogen atom, substituted or unsubstituted C1-C 10 An alkyl group, or an epoxy group;

[0050] n is a positive integer from 0 to 10;

[0051] L 1 is selected from an oxygen atom or a nitrogen atom;

[0052] L 2 is selected from an oxygen atom or a nitrogen atom;

[0053] X is selected from substituted or unsubstituted C1-C 10 Alkylene, substituted or unsubstituted C3-C 10 The cycloalkylene group, Or, a benzene ring.

[0055] Preferably, the glycidyl ether substance is one or more of the following monomers (a)-(m);

[0056]

[0057] The above structure (a) is the structure of glycerol triglycidyl ether.

[0058] The above structure (b) is the structure of pentaerythritol tetraglycidyl ether.

[0059] The above structure (j) is the structure of 1,4-butanediol diglycidyl ether.

[0060] The above structure (k) is the structure of trimethylolethane triglycidyl ether.

[0061] The above structure (1) is the structure of bisphenol A diglycidyl ether.

[0062] The above structure (m) is the structure of bisphenol F diglycidyl ether.

[0063] In some embodiments, the glycidyl ether material may be one or more polymers satisfying the following structural formula II:

[0064]

[0065] In structural formula II, R 2 is selected from hydrogen atom, substituted or unsubstituted C1-C 10 Alkyl, or

[0066] m is a positive integer from 2 to 40.

[0067] Preferably, the glycidyl ether substance is one or more of the following polymers (1)-(4);

[0068]

[0069] In some embodiments, the glycidyl ester substance may be one or more monomers satisfying the following structural formula III;

[0070]

[0071] In formula III, Y is selected from substituted or unsubstituted C1-C 10 Alkylene, substituted or unsubstituted C3-C 10 A cycloalkylene ring, or a benzene ring.

[0072] Preferably, the glycidyl ester substance is the following monomer (A) and / or (B);

[0073]

[0074] In some embodiments, the substance containing multiple epoxy groups is preferably one or more of the following monomers (I)-(IV);

[0075]

[0076] In some embodiments, the substance containing multiple epoxy groups is preferably a polyepoxy glycidyl ether monomer and / or a polyepoxy glycidyl ether polymer.

[0077] Wherein, the polyepoxy group glycidyl ether monomer may be glycerol triglycidyl ether and / or pentaerythritol tetraglycidyl ether.

[0078] Wherein, the polyepoxy glycidyl ether polymer may be polyglycerol glycidyl ether and / or polypentaerythritol tetraglycidyl ether.

[0079] In some embodiments, when the substance containing polyepoxy groups is a mixture of the polyepoxy glycidyl ether monomer and the polyepoxy glycidyl ether polymer, the mixed volume ratio of the polyepoxy glycidyl ether monomer and the polyepoxy glycidyl ether polymer may be (0.1-9):1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1 or 8:1. For example, a mixture of polyglycerol triglycidyl ether: pentaerythritol tetraglycidyl ether = 1:1, or polypentaerythritol tetraglycidyl ether: glycerol triglycidyl ether = 1:1.

[0080] In some embodiments, the molecular weight of the substance containing multiple epoxy groups may be 300-2000, such as a molecular weight of 550, a molecular weight of 700, a molecular weight of 1000, a molecular weight of 1200, a molecular weight of 1500, or a molecular weight of 1800.

[0081] In some embodiments, the raw material A may further include a substance containing a monoepoxy group. The substance containing a monoepoxy group refers to a substance containing one epoxy group in its structure.

[0082] The substance containing a monoepoxy group is preferably a monoepoxy glycidyl ether substance, or a monoepoxy glycidyl ester substance.

[0083] The monoepoxy glycidyl ether substance may be a substance having a conventional structure containing one epoxy group in the art, preferably phenyl glycidyl ether and / or butyl glycidyl ether.

[0084] The monoepoxy glycidyl ester substance may be one or more of phenyl glycidyl ether, butyl glycidyl ether, amyl glycidyl ether, octyl glycidyl ether, octadecyl glycidyl ether and naphthyl glycidyl ether, preferably phenyl glycidyl ether and / or butyl glycidyl ether.

[0085] In some embodiments, the raw material of the monolithic column includes porogen B.

[0086] In some embodiments, the porogen B is a solvent that is miscible with the substance A containing multiple epoxy groups and does not undergo polycondensation, preferably one or more of toluene, xylene, dichloromethane, dichloroethane, dioxane, formamide (DMF), dimethyl sulfoxide (DMSO) and methyl tert-butyl ether, more preferably one or more of toluene, dioxane and methyl tert-butyl ether, such as toluene and dioxane, toluene and methyl tert-butyl ether, or dioxane and methyl tert-butyl ether.

[0087] In some embodiments, when the porogen B is a mixture of two different substances, the volume ratio of the two different substances may be (0.1-9):1, such as 0.5:1, 1:1, 2:1, 3:1, 5:1 or 7:1.

[0088] In some embodiments, the weight of the raw material A is preferably 22%-70%, such as 25%, 30%, 35%, 40%, 45%, 50%, 55%, 58%, 65% or 68% of the total weight of the raw material A and the porogen B. The weight of the porogen B is preferably 35%-80%, such as 40%, 45%, 50%, 60%, 65%, 70%, 75% or 78% of the total weight of the raw material A and the porogen B.

[0089] In some embodiments, the raw material A is a polyepoxy glycidyl ether monomer and / or a polyepoxy glycidyl ether polymer; the porogen B is one or more of toluene, xylene, dichloromethane, dichloroethane, dioxane, formamide (DMF), dimethyl sulfoxide (DMSO) and methyl tert-butyl ether.

[0090] In some embodiments, the raw material A is a polyepoxy glycidyl ether polymer and a monoepoxy glycidyl ether monomer; the porogen B is one or more of toluene, xylene, dichloromethane, dichloroethane, dioxane, formamide (DMF), dimethyl sulfoxide (DMSO) and methyl tert-butyl ether.

[0091] In some embodiments, the raw material A is polypropylene triglycidyl ether and a monoepoxy glycidyl ether monomer; the porogen B is one or more of toluene, xylene, dichloromethane, dichloroethane, dioxane, formamide (DMF), dimethyl sulfoxide (DMSO) and methyl tert-butyl ether; the monoepoxy glycidyl ether monomer is preferably phenyl glycidyl ether and / or butyl glycidyl ether.

[0092] In some embodiments, the raw material A is polypropylene triglycidyl ether and monoepoxy glycidyl ether monomers; the porogen B is one or more of toluene, dioxane and methyl tert-butyl glyceryl ether; the monoepoxy glycidyl ether monomer is preferably phenyl glycidyl ether and / or butyl glycidyl ether.

[0093] In some embodiments, the raw material of the monolithic column includes catalyst C.

[0094] In some embodiments, the catalyst C may be a Lewis acid and / or a Lewis acid complex.

[0095] The Lewis acid may be one or more of aluminum trichloride, boron trifluoride, ferric bromide, ferric chloride, zinc chloride, niobium trichloride pentachloride and sulfur trioxide, such as boron trifluoride.

[0096] The Lewis acid complex may be one or more of boron trifluoride ethyl ether, boron trifluoride acetonitrile, boron trifluoride dimethyl carbonate and boron trifluoride ethylamine.

[0097] In some embodiments, the weight of the catalyst C is preferably 0.3‰-1‰, such as 0.4‰, 0.5‰, 0.6‰, 0.7‰, 0.8‰ or 0.9‰, based on the total weight of the raw material A and the porogen B.

[0098] In some embodiments, the raw material of the monolithic column includes a mercaptopyridine modifier D.

[0099] In some embodiments, the thiopyridine modifier D is in the form of HS-Py.

[0100] Wherein, Py is a substituted or unsubstituted pyridine ring; the substitution position of HS- on the pyridine ring is 2-, 3-, or 4-.

[0101] The unsubstituted pyridine ring, that is, the basic skeleton or the functional group to which the object is attached, has only hydrogen atoms or deuterium atoms thereof.

[0102] The substituents in the substituted pyridine ring are alkyl, cycloalkyl, heterocyclic, alkenyl, cycloalkenyl, alkynyl, aryl, heteroaryl, hydroxyl, thiol, alkoxy, alkylthio, aryl ether, aryl thioether, halogen, cyano, aldehyde, acyl, carboxyl, ester, amide, sulfonyl, sulfonate, sulfonamide, amino, nitro, and silane. The definitions of each group are the same as above.

[0103] The second aspect of the present invention provides a method for modifying a monolithic column.

[0104] The preparation method comprises the following steps:

[0105] S1. Hydroxylating the monolithic column;

[0106] S2. epoxidizing the hydroxylated monolithic column;

[0107] S3. Modify the epoxidized monolithic column with mercaptopyridine.

[0108] Wherein in step S1, hydroxylation comprises the following steps:

[0109] S11. Cleaning the monolithic column;

[0110] S12. Drying the monolithic column;

[0111] S13. Hydroxylated monolithic column;

[0112] S14. Post-processing.

[0113] In the step S11, a piece of the monolithic column is taken and eluted with deionized water with a volume of 10-20 times to remove the protective solution.

[0114] In step S12, the monolithic column is drained with a vacuum pump. The draining time is 10-120 min, preferably 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min. The draining temperature is 5-50°C, preferably 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C.

[0115] In the step S13, an acidic aqueous solution is added into the dried monolithic column, and the temperature is raised to react, so that the residual epoxy groups in the monolithic column are converted into hydroxyl groups.

[0116] The acid in the acidic aqueous solution is sulfuric acid, hydrochloric acid, nitric acid, formic acid, or acetic acid. The concentration of the acid in the acidic aqueous solution is 0.1-0.5M, preferably 0.2M, 0.3M, or 0.4M.

[0117] The volume ratio of the acidic aqueous solution to the monolithic column is (3-30):1, preferably 5:1, 7:1, 10:1, 15:1, 20:1, 25:1, 30:1.

[0118] The temperature-raising reaction is to raise the temperature of the system to 40-80°C and react for 1-6 hours. The temperature is preferably 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C. The reaction time is preferably 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h.

[0119] In the step S14, the hydroxylated monolithic column is rinsed with deionized water until the pH is neutral.

[0120] In some embodiments, after step S1, the epoxy group density of the whole column after hydroxylation is determined to be 0 or undetectable by epoxy group density measurement.

[0121] Wherein in step S2, epoxidation comprises the following steps:

[0122] S21. Cleaning the monolithic column;

[0123] S22. Drying the monolithic column;

[0124] S23. Epoxidized monolithic column;

[0125] S24. Post-processing.

[0126] In the step S21, a piece of the monolithic column is taken and eluted with deionized water with a volume of 10-20 times to remove the protective solution.

[0127] In step S22, the monolithic column is drained with a vacuum pump. The draining time is 10-120 min, preferably 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min. The draining temperature is 5-50°C, preferably 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C.

[0128] In the step S23, a solvent is added into the dried monolithic column, and epichlorohydrin is added after the column is fully soaked, and then a base is added, and the temperature is raised to react, so that the hydroxyl groups in the monolithic column are converted into epoxy groups.

[0129] The solvent is a DMSO:H2O mixed solvent, the ratio is 3:7-7:3, preferably 4:6, 5:5, 6:4. The volume ratio of the solvent to the monolithic column is (3-30):1, preferably 5:1, 7:1, 10:1, 15:1, 20:1, 25:1, 30:1.

[0130] The amount of epichlorohydrin added is 3-30% of the overall column, preferably 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%.

[0131] The alkali is one or more of sodium hydroxide, potassium hydroxide, and ammonia water, and the added amount is 0.5-5% of the whole column, preferably 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%.

[0132] The temperature-raising reaction is to raise the temperature of the system to 40-80°C and react for 1-8h. The temperature is preferably 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C. The reaction time is preferably 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, 6.5h, 7.0h, 7.5h.

[0133] In the step S24, the epoxidized monolithic column is rinsed with ethanol and deionized water until the pH is neutral.

[0134] Wherein in step S3, the mercaptopyridine modification comprises the following steps:

[0135] S31. A mixed solvent, a catalyst and a mercaptopyridine modifier D;

[0136] S32. The mixed solution of S31 is infiltrated into the monolithic column;

[0137] S33 mercaptopyridine modified monolithic column;

[0138] S34 post-processing.

[0139] In step S31, the solvent is an alcohol solvent, preferably one or more of methanol and ethanol. The amount of solvent added is 5-30mL / mL, preferably 5mL, 6mL, 7mL, 8mL, 9mL, 10mL, 11mL, 12mL, 13mL, 14mL, 15mL, 16mL, 17mL, 18mL, 19mL, 20mL, 21mL, 22mL, 23mL, 24mL, 25mL, 26mL, 27mL, 28mL, 29mL, 30mL.

[0140] The catalyst is sodium alcoholate, preferably one or more of sodium methoxide and sodium ethoxide. The concentration of the catalyst is 3-30 mol% of the solution, preferably 3 mol%, 4 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, 10 mol%, 11 mol%, 12 mol%, 13 mol%, 14 mol%, 15 mol%, 16 mol%, 17 mol%, 18 mol%, 19 mol%, 20 mol%, 21 mol%, 22 mol%, 23 mol%, 24 mol%, 25 mol%, 26 mol%, 27 mol%, 28 mol%, 29 mol%, 30 mol%.

[0141] The concentration of the mercaptopyridine modifier D in the solution is 1-10% (w / v), preferably 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0142] The step S31 may also use vibration, ultrasound or other methods to assist mixing.

[0143] In step S32, the epoxidized monolithic column prepared in step S2 is added to the mixed solution in step S31 to fully infiltrate the monolithic column. In step S32, vibration, ultrasound, vacuuming, etc. can also be used to assist in the infiltration.

[0144] In the step S33, the temperature is raised to allow the epoxy groups in the monolithic column to fully react with the mercaptopyridine modifier D.

[0145] The temperature-raising reaction is to raise the temperature of the system to 40°C-80°C and react for 10-36 hours. The temperature is preferably 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C. The reaction time is preferably 10h, 12h, 15h, 18h, 21h, 24h, 27h, 30h, 33h, 36h.

[0146] In step S34, the monolithic column is cooled and taken out, and rinsed with ethanol and deionized water until the pH is neutral.

[0147] After step S34 is completed, in order to protect the monolithic column, it can be stored in a 20%-70% ethanol solution for standby use.

[0148] The third aspect of the present invention provides an application of a monolithic column for enrichment and separation of DNA or RNA.

[0149] The monolithic column has the function of specifically adsorbing DNA or RNA. Specifically, it can specifically adsorb DNA and / or RNA in a mixed solution containing biomacromolecules, so that the DNA and / or RNA can be enriched in the monolithic column and then eluted and separated.

[0150] A fourth aspect of the present invention is to provide a chromatographic column comprising the aforementioned monolithic column.

[0151] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0152] The reagents and raw materials used in the present invention are commercially available.

[0153] The positive and progressive effects of the present invention are:

[0154] 1. The monolithic column prepared by the present invention is rich in hydroxyl groups and has excellent compatibility with elution objects containing biological macromolecules, and is particularly suitable for the field of biological macromolecule chromatography.

[0155] 2. The monolithic column prepared by the present invention retains the characteristics of excellent adsorption performance, uniform results, low operating pressure and high flow rate of epoxy resin monolithic column materials. The pores are adjustable, submicron-micron level, relatively uniformly distributed, and present a single-peak normal distribution, with high ligand utilization. The pores are through holes, without diffusion effect, no need to increase retention time, shorten process cycle, no obvious eddy current phenomenon, low shear force, no effect on sample load at high flow rate, and high toughness.

[0156] 3. The monolithic column prepared by the present invention has excellent specific adsorption capacity for nucleic acid substances and is suitable for the enrichment and separation of DNA and / or RNA substances. BRIEF DESCRIPTION OF THE DRAWINGS

[0157] Figure 1 This is the pore size distribution diagram of the integral column block prepared in Example 1.

[0158] Figure 2 This is the pore size distribution diagram of the integral column block prepared in Example 6.

[0159] Figure 3 This is a scanning electron microscope image of the integral column block prepared in Preparation Example 3.

[0160] Figure 4 This is a scanning electron microscope image of the integral column block prepared in Example 7.

[0161] Figure 5 This is a chromatography experiment diagram of the integral column block prepared in Example 1. DETAILED DESCRIPTION

[0162] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0163] Unless otherwise specified, the reagents used in the following examples and comparative examples are all conventional commercially available products in the art.

[0164] Preparation Example

[0165] S1. Hydroxylation: Take 1 mL of the monolithic column and wash it with deionized water for 20 times the volume on a sand core funnel to remove the protective liquid. Use a vacuum pump to drain the sand core funnel for 60 minutes at an ambient temperature of 25°C.

[0166] The 1 ml monolithic column block after being drained was transferred to a glass reaction bottle, and a 0.2 M deionized sulfuric acid solution was added, with the amount added being 10 ml of reaction solution / block (1 mL); ultrasonication was performed for 30 min to accelerate the rapid immersion of the reaction solution into the monolithic column block; after the ultrasonication, the glass reaction bottle was transferred to a water bath, heated to 60°C, and kept warm for 4 h; the hydroxylated monolithic column block was placed on a sand core funnel and rinsed with deionized water until the pH was neutral (6.5-7).

[0167] Through the epoxy group density measurement, it was determined that the block epoxy group density after hydroxylation was 0;

[0168] S2. Epoxidation: Take 1 mL of the hydroxylated monolithic column block, elute 20 times the volume of deionized water on a sand core funnel, and drain it on the sand core funnel with a vacuum pump for 60 minutes at an ambient temperature of 25°C.

[0169] After draining, transfer 1mL of the monolithic column block to a glass reaction bottle, first add solvent (50% DMSO deionized water solution), the amount added is 10mL / block (1mL); ultrasonic for 20 minutes to fully soak the monolithic block; then add epichlorohydrin, the amount added is 10% of the solvent mass, and continue ultrasonic for 30 minutes; finally add 2% sodium hydroxide, continue ultrasonic for 10 minutes, control the temperature at 20℃, and mix thoroughly. Move to a constant temperature water bath at 60℃, react for 6 hours; alternately rinse with ethanol and water for 20 times the volume of each block; vacuum dry after washing, dry and store at low temperature.

[0170] Table 1 Performance of Epoxidized Monolithic Column Block Preparation Example

[0171]

[0172] N: indicates that this step has not been processed

[0173] The average pore size of the samples 1 to 4 increases gradually through the determination of epoxy group density. After hydroxylation and then epoxidation, the epoxy group density decreases as the pore size increases.

[0174] Comparative Examples 1 and 2 are prepared by directly performing epoxidation treatment on Example 1 and Example 4 without hydroxylation, and the ligand density is significantly less than the value after epoxidation after the above hydroxylation. This indicates that a small amount of epoxy groups remain after the integral column is formed, and the epoxy groups in the original integral column are also converted into hydroxyl groups by hydroxylation. Together with the hydroxyl groups existing in the original integral column, they are used as reactants and converted into epoxy groups in the subsequent epoxidation step, thereby increasing the density of epoxy groups in the integral column. In addition, after hydroxylation and epoxidation, the flexibility of the epoxy groups increases, and there is a C3 connecting group between the epoxy groups and the integral column substrate, which enables the specifically adsorbed groups to extend from the substrate surface, thereby improving the capture capacity.

[0175] Example

[0176] Weigh 20 mol% of the reagent B described in Table 2, add it to the solvent C solution described in Table 2 (addition amount is 10 mL / mL), and mix thoroughly in a glass reactor. Weigh 5% (W / V) of the solvent mass of the reagent A described in Table 2, add it to the above solution, and mix thoroughly.

[0177] The epoxidized chromatographic stack was added to the above mixed solution and ultrasonicated for 15 minutes.

[0178] The reaction mixture was then placed in a water bath shaker, heated to 60°C, with a shaking frequency of 100 rpm, and shaken for 24 h.

[0179] After the reaction is completed, the monolithic column is taken out and washed alternately with ethanol / deionized water until the pH of the droplet is neutral, and the monolithic column is placed in 20% ethanol for storage.

[0180] Table 2 Examples and Comparative Examples

[0181]

[0182]

[0183]

[0184] Effect test

[0185] Pore ​​size distribution, pore volume, and porosity determination

[0186] Test method: Mercury intrusion method

[0187] Test equipment: USA-McMerrittick-autoporeV 9620

[0188] Test results:

[0189] From the results of the examples, the pore parameters were basically kept normal through the click chemistry coupling of thiol and epoxy. There was no pore collapse, blockage or other abnormal phenomena. It can be seen that this method can successfully prepare the monolithic column modified with thiol pyridine without affecting its basic properties such as pore size distribution, pore volume, and porosity.

[0190] Table 3 Pore size distribution, pore volume, porosity test results

[0191]

[0192] Figure 1 This is the pore size distribution diagram of Example 1, Figure 2 This is the pore size distribution diagram of Example 6. It can be seen from the figure that the pore size distribution after modification is concentrated and there is no obvious change in the pore size distribution. It can be seen that the modification step has no effect on basic properties such as pore size.

[0193] Field emission electron microscope scanning test

[0194] Test object: Preparation Example 3, Example 7

[0195] Test equipment: Germany-Zeiss sigma300, Oxford spectroscopy.

[0196] Test results:

[0197] Figure 3 To prepare the electron microscope image of Example 3; Figure 4 The electron microscope image of Example 7 is shown in Figure 3. Preparation Example 3 and Example 7 are both monolithic columns modified with epoxidation and quaternary ammonium salt, each with a pore size of about 4.2 μm. By comparing the electron microscope images, the pore structure is normal after thiopyridine modification, which is consistent with the porous structure of the unmodified monolithic column.

[0198] Epoxy ligand density determination

[0199] Test objects: Preparation examples 1-4 and comparative examples 1-2 in Table 1

[0200] Test method: Sodium thiosulfate-hydrochloric acid titration method.

[0201] The chromatographic materials of Preparation Examples 1-4 and Comparative Examples 1-2 modified by epoxy were cleaned with deionized water, placed in a sand core funnel and vacuum-dried for 10 minutes, and then weighed 1 piece (about 0.5g) and placed in a ground-mouth conical flask, 3mL, 1.3mol / L sodium thiosulfate and 1-2 drops of phenolphthalein indicator were added, and the conical flask was sealed and placed at room temperature for 1 hour. The supernatant solution after the reaction was titrated with 0.1mol / L hydrochloric acid standard solution until the red solution became colorless. Substitute the consumed volume of hydrochloric acid standard solution into the following formula to calculate the epoxy ligand density:

[0202] S=1000*[M HCl (V0-V1)*ρ / W]

[0203] S: epoxy ligand density, μmol / mL;

[0204] M HCl : hydrochloric acid concentration, mmol / L;

[0205] V0, V1: volume of HCl before and after titration, mL;

[0206] ρ: medium density (1.2 g / mL);

[0207] W: The mass of the whole block weighed (g).

[0208] Test equipment: acid-base titration device.

[0209] Test results: See Table 1.

[0210] 15000bp large plasmid loading and yield test

[0211] Test object: Examples 1-22

[0212] Test method: as follows

[0213] 3.1. Anion exchange chromatography stacks (DEAE-Plus) were placed in 1 mL radial flow chromatography tooling (Yuji Bio-Chromatography Tooling);

[0214] 3.2. Connect the chromatography tool containing the PYSH block to the liquid chromatography equipment, use the balancing solution: 50mM Tris-HCl+10mM EDTA+2.5-3M (NH4)2SO4, pH7.2-7.4, balance 5-10 times the volume of the column until the conductivity, pH, and UV baselines are stable;

[0215] 3.3. Take a plasmid sample (pHelper-CA plasmid DNA (about 15000bp, provided by Kaituo Biotechnology), supercoiled plasmid purity 90%), dilute it to 1 mg / mL with a balance, and inject 5 mL through the chromatography equipment injection system at a flow rate of 3-5 mL / min;

[0216] 3.4 Elution with eluent E (50 mM Tris-HCl + 10 mM EDTA + 1.7 M (NH4)2SO4 + 0.3 M NaCl) at a flow rate of 2-3 mL / min;

[0217] 3.5. Regeneration: First, use deionized water to regenerate the chromatographic stack (PYSH) column at a flow rate of 2-3 mL / min; then use 1M sodium hydroxide to clean the column, and immediately wash the column with deionized water until it is neutral.

[0218] Test results: See Table 4

[0219] Table 4 15000bp large plasmid loading and yield test results

[0220]

[0221]

[0222] For Examples 1-6, after the 2.7 μm chromatographic stack monolithic column block is modified, the yield is 50%-60%; the loading capacity is ≥4.5 mg, and it is judged by Example 1 that the sample is not supersaturated, and the part of the flow-through FT is an open-loop plasmid (that is, during the injection process, the mobile phase can be adjusted to make the impurities flow through during the injection process, which indirectly improves the utilization rate of the monolithic column, such as Figure 5 As shown). The conventional microsphere mercaptopyridine method is a classic three-step chromatography method of agarose microspheres, including molecular sieves, 2-mercaptopyridine modified fillers and anion exchange microspheres. When the 2-mercaptopyridine filler is used to purify ultra-large molecular plasmid DNA, the microsphere filler needs to complete the chromatography through the diffusion effect, and the yield and loading capacity are both low. The yield is generally 30-40%, and the loading capacity is 1mg-2mg / mL. This type of filler column is generally suitable for separating plasmid molecules below 6000bp.

[0223] Similar monolithic column materials, such as high-density C4 polymethacrylate monoliths, separate supercoils through hydrophobic interactions, and loading requires high salt concentrations to increase hydrophobic interactions. Plasmid purification by mercaptopyridine is also called sulfur affinity because it contains a pyridine ring and a carbon-sulfur bond. The pyridine ring can provide a certain hydrophobic effect, and N can provide ionic and hydrogen bonding effects. Sulfur is also a strong electrophilic group. Compared with open-loop plasmids, supercoiled plasmids have a stronger topological compressed helical configuration, which makes the hydrogen bonding, hydrophobicity of the bases, and the charge density of the phosphate backbone relatively high, so separation can be achieved through this difference.

[0224] In Examples 7-12, the 4.2 μm chromatographic stack monolithic column blocks were modified with mercaptopyridine, with a yield of 88%-90% and a loading of 3-4 mg. In Examples 13-18, the 5.2 μm chromatographic stack monolithic column blocks were modified with mercaptopyridine, with a yield of 92%-97% and a loading of 1-2 mg.

[0225] As can be seen from Table 4, as the pore size increases, the overall loading capacity gradually decreases and the yield gradually increases. The purity of the supercoiled plasmid has been improved on the basis of the original 90%, indicating that the open-ring plasmid has a certain enrichment and separation effect on several coupled ligands. In terms of separation effect, 2-mercaptopyridine (Examples 1, 7, 13, 19-22), 4-mercaptopyridine (Examples 2, 8, 14), and 2-mercapto-6-methylpyridine (Examples 4, 10, 16) are basically all above 95% pure. The purity of several other pyridine extension compounds has been correspondingly improved, with a small increase of about 2%. The possible reason is that the nitro, carboxyl, and sulfonamide on the pyridine ring change the hydrophobicity, polarity, hydrogen bonding, and ionic bonding of the overall ligand. Although the separation degree can be optimized by chromatographic process conditions, there is an impossible triangle relationship between purity, loading capacity or efficiency, and yield, which needs to be balanced with each other, which is difficult. 2-Mercaptopyridine, 4-mercaptopyridine and 2-mercapto-6-methylpyridine can meet the purification requirements.

Claims

1. A monolithic column, characterized in that: Pyridine groups are grafted on the inner surfaces of the pores and channels of the monolithic column.

2. The integral column according to claim 1, characterized in that: The pyridyl group exists in the form of EP-OCH2CH(OH)CH-SPy; in: EP is epoxy resin, Py is a substituted or unsubstituted pyridine ring; The substituents in the substituted pyridine ring are alkyl, cycloalkyl, heterocyclic, alkenyl, cycloalkenyl, alkynyl, aryl, heteroaryl, hydroxyl, thiol, alkoxy, alkylthio, aryl ether, aryl thioether, halogen, cyano, aldehyde, acyl, carboxyl, ester, amide, sulfonyl, sulfonate, sulfonamide, amino, nitro, and silane.

3. The integral column according to claim 2, characterized in that: In some embodiments, the substituent in the substituted pyridine ring is methyl, sulfonamide, carboxyl or nitro.

4. The integral column according to any one of claims 1 to 3, characterized in that: The pore size of the monolithic column is 2 μm-6 μm, preferably 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm , 3.9μm, 4.0μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm , 5.0μm, 5.1μm, 5.2μm, 5.3μm, 5.4μm, 5.5μm, 5.6μm, 5.7μm, 5.8μm, 5.9μm, 6.0μm; The pore volume of the monolithic column is 1.1 mL / g-1.8 mL / g, preferably 1.10 mL / g, 1.15 mL / g, 1.20 mL / g, 1.25 mL / g, 1.30 mL / g, 1.35 mL / g, 1.40 mL / g, 1.45 mL / g, 1.50 mL / g, 1.55 mL / g, 1.60 mL / g, 1.65 mL / g, 1.70 mL / g, 1.75 mL / g, 1.80 mL / g; The porosity of the integral column is 55%-68%, preferably 55.0%, 55.5%, 56.0%, 56.5%, 57.0%, 57.5%, 58.0%, 58.5%, 59.0%, 59.5%, 60.0%, 60.5%, 61.0%, 61.5%, 62.0%, 62.5%, 63.0%, 63.5%, 64.0%, 64.5%, 65.0%, 65.5%, 66.0%, 66.5%, 67.0%, 67.5%, 68.0%.

5. The integral column according to any one of claims 1 to 4, characterized in that: The raw materials of the monolithic column include a substance A containing multiple epoxy groups, a porogen B, and a mercaptopyridine modifier D; The mercaptopyridine modifier D exists in the form of HS-Py; Wherein, Py is a substituted or unsubstituted pyridine ring; the substitution position of HS- on the pyridine ring is 2-, 3-, or 4-.

6. A method for preparing a monolithic column according to any one of claims 1 to 5, characterized in that: The steps include: S1. Hydroxylating the monolithic column; S2. epoxidizing the hydroxylated monolithic column; S3. Modify the epoxidized monolithic column with mercaptopyridine.

7. The preparation method according to claim 6, characterized in that: The step S1 comprises: S13. Add an acidic aqueous solution into the dried monolithic column and heat the reaction to convert the residual epoxy groups in the monolithic column into hydroxyl groups.

8. The preparation method according to any one of claims 6 to 7, characterized in that: The step S2 comprises: S23. Add solvent into the dried monolithic column, add epichlorohydrin after it is fully soaked, and then add alkali, and heat the reaction to convert the hydroxyl groups in the monolithic column into epoxy groups.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The step S3 comprises: S31. A mixed solvent, a catalyst and a mercaptopyridine modifier D; S32. The mixed solution of S31 is infiltrated into the monolithic column; S33 mercaptopyridine modified monolithic column; The solvent in step S31 is an alcohol solvent, preferably one or more of methanol and ethanol; The catalyst is sodium alkoxide, preferably one or more of sodium methoxide and sodium ethoxide.

10. Use of the monolithic column according to any one of claims 1 to 5 or the monolithic column prepared by the preparation method according to any one of claims 6 to 9 for enrichment and separation of DNA or RNA.

11. A chromatographic column, characterized in that: It comprises the monolithic column as described in any one of claims 1 to 5 or the monolithic column prepared by the preparation method as described in any one of claims 6 to 9.

Citation Information

Patent Citations

  • Hydrophilic integral material as well as preparation and application thereof

    CN113145088A

  • Chromatographic material raw material composition, chromatographic material, preparation method and application of chromatographic material, monolithic column and chromatographic pile

    CN118179462A

  • Monolithic column having immobilized monomeric avidin for enriching and identifying biotinylated species

    EP2485836A1

Cited By

  • Mercaptopyridine modified monolithic column

    WO2025232849A1